Integrating Quantitative and Qualitative Methods to Evaluate an Online Psychoeducational Program for Sexual Difficulties in Colorectal and Gynecologic Cancer Survivors. Issue 7 (3rd October 2017) - Brotto, Lori A.; Dunkley, Cara R.; Breckon, Erin; Carter, Jeanne; Brown, Carl; Daniluk, Judith; Miller, Dianne
Abstract : Sexual health is an integral component of quality of life for cancer survivors, and is often negatively impacted by treatment. Geographic limitations often prohibit survivors from accessing sexual health programs designed to address their needs. This study examined the efficacy of an online, 12-week psychoeducational program, which included elements of mindfulness meditation, for sexual difficulties in survivors of colorectal or gynecologic cancer. Complete pre- and postintervention data were available for 46 women (mean age 55.0, SD 9.6) and 15 men (mean age 59.7, SD 6.8). Women experienced significant improvements in sex-related distress ( p < .001), sexual function ( p < .001 and p < .01), and mood ( p < .001); these results were maintained at six months follow-up. Men's improvement in desire was not significant ( p = .06), whereas intercourse satisfaction was ( p < .05) immediately after the program, but not at follow-up. In order to more fully explore women's experiences, interviews were carried out with six participants and analyzed using narrative inquiry. Women shared a feeling of renewed hope for regaining their sex lives, and expressed that they would have valued an interactive component to the program. These findings suggest that an online, unidirectional psychoeducational program is feasible, and may be effective for women survivors of gynecologic and colorectal cancer, but further work is needed to ensure that online interventions address the sexual health needs of male survivors.